2015
DOI: 10.1371/journal.pone.0132446
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Inhibitor of Complement C1 (PIC1) Rapidly Inhibits Complement Activation after Intravascular Injection in Rats

Abstract: The complement system has been increasingly recognized to play a pivotal role in a variety of inflammatory and autoimmune diseases. Consequently, therapeutic modulators of the classical, lectin and alternative pathways of the complement system are currently in pre-clinical and clinical development. Our laboratory has identified a peptide that specifically inhibits the classical and lectin pathways of complement and is referred to as Peptide Inhibitor of Complement C1 (PIC1). In this study, we determined that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 25 publications
(62 reference statements)
1
64
0
Order By: Relevance
“…To confirm that the hemolysis was occurring via antibodyinitiated complement activation, we tested whether PIC1, which inhibits classical pathway activation by preventing enzymatic activation of C1, 11,12 could inhibit the high degree of hemolysis resulting from Donor 1 plasma mixed with B1 RBCs. The addition of PIC1 dose dependently inhibited the hemolysis of Donor 1 plasma by up to 97% (p 5 0.013) (Fig.…”
Section: Confirmation Of Antibody-initiated Complement Pathway Activamentioning
confidence: 99%
“…To confirm that the hemolysis was occurring via antibodyinitiated complement activation, we tested whether PIC1, which inhibits classical pathway activation by preventing enzymatic activation of C1, 11,12 could inhibit the high degree of hemolysis resulting from Donor 1 plasma mixed with B1 RBCs. The addition of PIC1 dose dependently inhibited the hemolysis of Donor 1 plasma by up to 97% (p 5 0.013) (Fig.…”
Section: Confirmation Of Antibody-initiated Complement Pathway Activamentioning
confidence: 99%
“…In a very interesting finding, Sharp et al noted that while a 15 amino acid peptide derivative was able to block CP activation it was unable to displace C1r 2 C1s 2 from the C1 complex, unlike the in-tact HAstV-1 Coat Protein macromolecule (68). These observations strongly suggest that complete displacement of C1r 2 C1s 2 is not required to inhibit C1, but rather that HAstV-1 Coat Protein likely exerts its inhibitory effect by disrupting the orientation of C1q relative to C1r 2 C1s 2 within the C1 complex.…”
Section: Disruption Of the C1 Complexmentioning
confidence: 99%
“…To this point, small peptide mimics of S. aureus SCIN-derived AP inhibitors have been reported (115), and a peptidic derivative of HAstV-1 Coat Protein (PIC1) has shown efficacy as complement inhibitor in in vivo (68, 116). The ability of SCIN-derived peptides and PIC1 to preserve the inhibitory activities present in full-length proteins is consistent with the idea that immune evasion molecules, which often appear to target relatively small functional “hot-spots” on their host targets, hold promise as templates for drug design.…”
Section: Perspectivesmentioning
confidence: 99%
“…The demonstration of differential adipokine, cytokine and chemokine protein profile in control, lean and diet-induced obese mice may have implications for immune responsiveness and risk of disease [50]. Sharp JA et al, (2015) reported that, the complement system has been increasingly recognized to play a pivotal role in a variety of inflammatory and autoimmune diseases. Consequently, therapeutic modulators of the classical, lectin and alternative pathways of the complement system are currently in pre-clinical and clinical development [51].…”
Section: Obesity and Cytokines:-mentioning
confidence: 99%